Peningkatan Hasil Belajar Pada Sistem Pembelajaran Melalui Model Project Based Learning Berbantuan Platform Zoom Meeting - DIta, Marvinda Rizki (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2020)
This Classroom Action Study was aimed at describing the online learning outcomes improvement and learning process of Grade V students in SD Negeri 1 Pecangaan Â through projects based learning models with using of Zoom Aplication. The research was conducted through two cycles of action. The diagram shows that the exhaustiveness increased from cycle I at 47% to 88% after cycle II. The learning outcomes also improved from cycle I to II at 63.8 and 82.9 respectively. This study concluded that through the using of Zoom Application, there will be improvement at online learning outcomes in thematic learning.